(untitled) - Manunu, Bayanika

Determination of the mechanism of synergy of SQ109 with rifampicin and isoniazid in Mycobacterium smegmatis (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015